Clinical Outcomes and Testosterone Levels Following Continuous Androgen Deprivation in Patients with Relapsing or Locally Advanced Prostate Cancer: A Post Hoc Analysis of the ICELAND Study - Tombal, Bertrand; Cornel, Erik; Persad, Raj; Stari, Anny; Gómez Veiga, Francisco; Schulman, Claude (2017)
Purpose: Lower serum testosterone levels correlate with improved cause specific survival and longer time to progression in year 1 of continuous androgen deprivation in men with prostate cancer. ICELAND was a large European study demonstrating the efficacy of leuprorelin (Eligard®) during continuous androgen deprivation. In this post hoc analysis we investigated serum testosterone levels within year 1 of continuous androgen deprivation to determine survival and time to progression. Materials and Methods: In ICELAND (ClinicalTrials.gov NCT00378690) patients with locally advanced or relapsing nonmetastatic prostate cancer and with prostate specific antigen 1 ng/ml or less following 6-month induction with leuprorelin 3-month depot 22.5 mg (plus bicalutamide 50 mg per day for 1 month) were randomized 1:1 to continuous androgen deprivation (361) or intermittent androgen deprivation (340) with leuprorelin for 36 months. Patients receiving continuous androgen deprivation were stratified by minimum, median and maximum testosterone levels during year 1 of therapy into 20 or less, greater than 20 to 50 and greater than 50 ng/dl subgroups. Cause specific survival and time to prostate specific antigen (castrate resistant prostate cancer) progression were analyzed. Results: A total of 90.1%, 83.5% and 74.5% of patients receiving continuous androgen deprivation achieved minimum, median and maximum serum testosterone levels of 20 ng/dl or less, respectively. Cause specific survival rates and time to prostate specific antigen progression did not differ among the testosterone subgroups. Conclusions: In patients receiving continuous androgen deprivation cause specific survival and time to prostate specific antigen progression did not differ according to testosterone levels in year 1 of therapy. This finding may in part be due to the induction period and the effectiveness of leuprorelin in lowering testosterone. SCOPUS: ar.j info:eu-repo/semantics/published